2016
DOI: 10.4103/2231-0762.192934
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of antibacterial efficacy of coconut oil and chlorhexidine on Streptococcus mutans: An : An in vivo study study

Abstract: Aims:Streptococcus mutans is the most common organism causing dental caries. Various chemotherapeutic agents are available that help in treating the bacteria, with each having their own merits and demerits. Recent research has shown that coconut oil has anti-inflammatory and antimicrobial action. Therefore, the present was conducted to determine the antibacterial efficacy of coconut oil and to compare it with chlorhexidine.Materials and Methods:A total of fifty female children aged 8–12 years were included in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 25 publications
1
43
1
1
Order By: Relevance
“…A study by Peedikayil et al on children aged 8−12 also showed that VCO is as effective as chlorhexidine in decreasing the number of S. mutans in saliva and plaque [11]. However, in this study, the antibacterial effect of 12.5% CO mouthwash was not observed.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…A study by Peedikayil et al on children aged 8−12 also showed that VCO is as effective as chlorhexidine in decreasing the number of S. mutans in saliva and plaque [11]. However, in this study, the antibacterial effect of 12.5% CO mouthwash was not observed.…”
Section: Discussioncontrasting
confidence: 74%
“…that compared the effectivity of VCO, chlorhexidine, and aquades in decreasing the colony counts of S. mutans. It showed that VCO and chlorhexidine could significantly decrease colony counts of S. mutans, while there was no decrease in S. mutans colony counts after using aquades [11].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…count. 43 Another randomized controlled study was done by Kaushik et al in 2016 with a sample size of 60. The subjects were divided into three groups, Group A: Oil pulling, Group B: Chlorhexidine, and Group C: Distilled water.…”
Section: Studies Related To Effects Of Coconut Oil Pulling On Oral Hementioning
confidence: 99%
“…Another in vivo study comparing the antibacterial efficacy of Coconut oil and Chlorhexidine on Streptococcus mutans, concluded that Coconut oil has the same effect as Chlorhexidine on SM (21) .…”
Section: Introductionmentioning
confidence: 99%